Sequential analysis methods in genomic scans - Province, Michael (Henry Stewart Talks, 2007)
Sequential analysis in genome wide linkage and association scans, Sequential probability ratio test, Sequential multiple decision procedures, Simulation results and examples
Archived at 2021/02/25